2014
DOI: 10.1039/c3cp55108c
|View full text |Cite
|
Sign up to set email alerts
|

A bolaamphiphilic amino acid appended photo-switching supramolecular gel and tuning of photo-switching behaviour

Abstract: Self-assembled bolaamphiphilic perylene bisimide (PBI) containing an amino acid appended fluorescent semiconducting soft material (hydrogel) has been discovered at physiological pH. This new organic material based on self-assembled perylene bisimide appended amino acid-based bolaamphiphile (PBI-C11-Y) has been well characterized using various techniques including UV-Vis, fluorescence, X-ray diffraction, FT-IR, transmission electron microscopic (TEM) and atomic force microscopic (AFM) studies. Interestingly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 72 publications
1
31
0
Order By: Relevance
“…The authors demonstrated that the incorporation of graphene oxide or reduced graphene oxide into the hydrogels enhances the photoresponsiveness of the hydrogel of 106 . 391 Zang et al also reported that a perylenebisimide derivative ( 107 ) forms a hydrogel via pH triggering. The authors found that the addition of hydrochloric acid in the 4.4 mM (about 0.2 wt %) solution of 107 (in the presence of 26.4 mM triethylamine) results in a dark red hydrogel, 392 which agrees with the formation of a charge transfer complex.…”
Section: Molecular Designmentioning
confidence: 99%
“…The authors demonstrated that the incorporation of graphene oxide or reduced graphene oxide into the hydrogels enhances the photoresponsiveness of the hydrogel of 106 . 391 Zang et al also reported that a perylenebisimide derivative ( 107 ) forms a hydrogel via pH triggering. The authors found that the addition of hydrochloric acid in the 4.4 mM (about 0.2 wt %) solution of 107 (in the presence of 26.4 mM triethylamine) results in a dark red hydrogel, 392 which agrees with the formation of a charge transfer complex.…”
Section: Molecular Designmentioning
confidence: 99%
“…photo-switching can be seen in the current over time as the light source is turned on and off (Figure1.22b). Similar results with photo-switching behavior were seen for a gel made from a bolaamphiphile amino acid comprised of a tyrosine moiety tethered to the PDI core by a hydrophobic 11-carbon alkyl linker 77. …”
supporting
confidence: 75%
“…Like the previous semiconducting gel example from Muthusamy et al, the optoelectronic response of this gel can be tuned with the inclusion of graphene. Specifically, incorporation of graphene oxides into the gel allows for a more distinct “on” current state to be accessed upon white light exposure, opening the possibility of a logic gate-esque system based on these self-assembled gels [25]. However, such a material was only shown to cycle four times before a roughly 33% degradation in distinction between “on” and “off” states.…”
Section: Supramolecular Gels For Optoelectronic Applicationsmentioning
confidence: 99%
“…Selected gelators developed for optoelectronic applications: ( A ) a conductive, self-healing PNAGA-PAMPS/PEDOT/PSS-3-49 gelator [21]; ( B ) a fluorescent gelator with hydrophobic moieties of pyrenebutyric acid and a hydrophilic moiety of an ethyleneoxy unit coupled with 1-(3-aminopropyl)imidazole [23]; ( C ) a photocatalytic chromophore amphiphile gelator [24]; and ( D ) a dipeptide-based perylene bisimide derivative gelator whose xerogel exhibits current photo-switching properties [25]. …”
Section: Figurementioning
confidence: 99%